Peran Nazhir Dalam Mengelola dan Mengembangkan Tanah Wakaf Tanpa Dokumen Legalitas - Nur Hishaly GH; Muhammad Syaiful Bahri; Nasri Hamang; Firman (Indonesia Journal Of Zakat And Waqf, 2023)
The purpose of this research is to provide a description of the management and development of waqf land that does not yet have legal documents such as certificates. The second objective of this research is to describe the role of the nazir as the mandate holder of the waqif in terms of making efforts to arrange legal documents. This research uses a qualitative approach and collects data using field research methods, with data collection techniques through interviews. The results showed that the management and development of waqf land that does not yet have legal documents are in accordance with the designation and intention of the waqif to build a mosque on the waqf land. The mosque as a means of worship is also developed as a Qur'an Education Park and a place to commemorate Muslim religious days. The role of the nazir in safeguarding the waqif's property is not yet optimal, this is indicated by the fact that administratively the document is not yet in the hands of the nazir as the custodian of the waqf land. This finding has implications so that waqf practices can be carried out in accordance with applicable legal provisions so that they will not cause problems in the future.